Testing the convergent- and predictive validity of a multi-dimensional belief-based scale for attitude towards personal safety on public bus/minibus for long-distance trips in Ghana: A SEM analysis. (January 2020) - Sam, Enoch F.; Brijs, Kris; Daniels, Stijn; Brijs, Tom; Wets, Geert
Abstract: We examined the predictive validity of the public bus passenger safety attitude scale (PBPSAS), a measure of personal safety attitude (PSA), to predict future intention to use public bus/minibus for long-distance trips. Using 510 adults, we tested among other things the hypothesis that PSA has a positive significant effect on future intentions to use public bus/minibus for long-distance trips. Data analyses involved: (1) descriptive analyses of measure reliabilities and the strength and evaluation of people's safety-related beliefs, (2) fitting measurement and structural models to determine the factorial structure of PSA and (3) path analysis to examine the relationships between two different measures for personal safety-related attitude (indirect (belief-based) measure for PSA and a direct measure) and future intentions to use public bus/minibus for long-distance trips. Data analyses were conducted using IBM SPSS Statistics 25 and AMOS 24. We found that: (1) a second-order factor model provides a more parsimonious framework for explaining PSA than a three-factor model, (2) the indirect measure for attitude towards personal safety has convergent validity, (3) PSA has a positive significant effect on both a direct measure for attitude towards personal safety on public bus/minibus, and future intention to use public bus/minibus for long-distance trips and (4) that the direct measure for attitude towards personal safety also has a positive significant effect on the future intention to use public bus/minibus. We thus conclude that PBPSAS is a useful instrument for measuring PSA and is valid in predicting future intentions to use public bus/minibus for long-distance trips. Highlights: Second-order factor model is parsimonious in explaining personal safety attitude. Beliefs-based measure for personal safety attitude has convergent validity. Personal safety attitude significantly predicts attitude towards personal safety. Personal safety attitude significantly predicts future intention to use PT.